Development of a Modular Cadaveric Endoscopic Orbital Surgery Model. Issue 2 (March 2020) - Banks, Catherine; Husain, Qasim; Sacks, Raymond; Freitag, Suzanne K.; Bleier, Benjamin S.
Introduction: Endoscopic orbital surgery requires the acquisition of unique skill set including endoscopic bimanual dissection of intra/extraconal lesions adherent to orbital fat and neurovascular structures. Our goal was to develop a modular cadaveric model used to train surgeons to resect orbital pathology within any desired orbital compartment. Methods: Expansile superabsorbent polymer (SAP) beads (2 mm) were soaked in Omnipaque™ (Iohexol) solution for 15 minutes prior to transcaruncular orbital implantation using 10-gauge angiocath. Insertion depth was designed to implant beads in predetermined intraconal compartments corresponding to established orbital tumor stages. Beads were left to expand in situ over a period of 1 to 5 hours. Computed tomography scans were performed using the FUSION image guidance protocol. Model utility and learning curves were assessed by quantifying resection time over 8 sequential attempts. Results: All 24 beads were successfully implanted in 8 orbits corresponding to CHEER stage II to IV lesions (n = 3 per orbit). Beads expanded from 2 mm to an average of 5.2 mm within 1 hour. During expansion, the beads interpolated into the adjacent fascia similar to in vivo tumors. Average insertion time was 5:53 minutes per orbit (range, 3:24–10:33 min) and average time to bead identification was 10:47 minutes. Across all beads, dissection times decreased in a nonsignificant manner over 8 consecutive attempts. Conclusion: The directed implantation of expansile SAP beads in this cadaveric model accurately replicates the approach, identification, and resection of isolated orbital lesions. This orbital model can assist the endoscopic surgical team to develop further knowledge and technical skill sets to approach orbital lesions. Further ongoing studies to validate this model are currently underway.